Of norms and words: in order to think school in a performative code - Tuillang, Yuing Alfaro (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article explores a hypothesis stating that the performative character of norms offers many important points to think school. Thus, in the first place it is checked Canguilhem’s contributions related to the way the normative development works, and how it has to do with historical institutional processes in which school plays a key role. Besides, it is appealed to Foucault and Esposito’s inquiries which complement such contributions in the institutional field, showing the productive and performative character of norms. Finally, some contributions by Rancière related to the explanatory order and the prominence of teacher’s word as basis and support of school institutions are analyzed. Instead of conclusions, the convergence of these ideas allows to state suggestions generating analysis perspectives in order to think pedagogy and schooling from a perspective in which the constitutive value of norms sheds light on the crossing of relations between knowledge and power.